SINERGI POTENSI, PROGRAM, DAN ANGGARAN: SUATU UPAYA AKSELERASI PENGURANGAN KEMISKINAN DAN PENGANGGURAN - Ika Rahutami; Rini Hastuti (JURNAL LITBANG PROVINSI JAWA TENGAH, 2010)
Regional development needs economic potential, program and budget synergy. Based on theory and best practice from other regions, stated that the synergy of economic potential, program and budget are important to reduce poverty and unemployment. This research is purposed to (i) analyze priority sector based on actual economic potential and condition; (ii) Analyze the gap between actual economic potential and condition with mentioned program in RKPD; (iii) analyze budget performance; and (iv) Evaluate the gap between programs and budgeting. This research was conducted in Semarang and Wonosobo regencies. Qualitative and quantitative analysis were used to test budget performance by using value for money concept or triple E (economic, effective and efficient). The analyzed data for Semarang indicated that the dominant sectors are agriculture, industry and trade. General evaluation of budgeting program showed that there was unsynchronized data in poverty measurement. This condition caused the budgeting process related to the reduction of poverty and unemployment became difficult. The positive finding was most of the analyzed activity programs were economic and efficient. Unfortunately, there was less available data related to the outcome. The data of Wonosobo showed that agriculture is the dominant sector. The budget performance showed that there weren’t plenty idea about option for the poor and unemployment. Fragmentation in the inception of budgeting also caused activities being intended for poverty and unemployment reduction became very limited. It was found that Wonosobo was good evaluated with triple E aspect.